2020
DOI: 10.1101/2020.07.01.181669
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Task specialization across research careers

Abstract: We model a set of 70,694 publications and 347,136 distinct authors using Bayesian networks to predict scientists’ specific contributions on each of their publications. We predict the contributions of 222,925 authors in 6,236,239 publications, and apply an archetypal analysis to profile scientists by career stage. We divide scientific careers into four stages: junior, early-career, mid-career and late-career. Three scientific archetypes are found throughout the four career stages: leader, specialized, a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Several decades of research, across many fields, show that men typically publish more papers than women (1-3), but the reasons for and consequences of this difference remain uncertain. Explanations are numerous and include the hiring of women at lower-ranked and less-productive institutions (4-6), higher teaching and service loads (2,7,8), differences in research or task specialization (9,10), more time invested in drafting initial results (11,12), shorter career lengths (13), and the greater impact of childbearing and parenthood on women. Of these factors, parenthood affects a majority of faculty, both women and men, yet studies of its effect on scientific productivity are contradictory, finding negative (14)(15)(16), positive (17), or no relationship (11,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Several decades of research, across many fields, show that men typically publish more papers than women (1-3), but the reasons for and consequences of this difference remain uncertain. Explanations are numerous and include the hiring of women at lower-ranked and less-productive institutions (4-6), higher teaching and service loads (2,7,8), differences in research or task specialization (9,10), more time invested in drafting initial results (11,12), shorter career lengths (13), and the greater impact of childbearing and parenthood on women. Of these factors, parenthood affects a majority of faculty, both women and men, yet studies of its effect on scientific productivity are contradictory, finding negative (14)(15)(16), positive (17), or no relationship (11,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing the positions of authorship in Science and Humanities, West et al (2013) found that when men and women collaborate together, men tend to take the leading role as the first or last author. The specific division of labor for different genders has been identified by Robinson-Garcia et al (2020) that women perform specialized tasks (e.g., experiments and analyzing data) by contrast men perform supporting and leading tasks (e.g., designing and writing). Meanwhile, females have a homophily preference to work among the same genders and countries (Uhly et al, 2017) which can lead to diminishment in creative ideas and fewer citations (Larivière et al, 2013).…”
Section: Team Power Dynamics and Related Factorsmentioning
confidence: 99%
“…These connections thus become vital to updating tasks, where a combination of different expertise is essential to ensure the completion of increasingly complex research projects. However, this also may lead researchers to become narrow specialists (Robinson-Garcia et al 2020) who are less able to recognize relationships between separate groups of phenomena. The increased specialization of researchers combined with the need for attracting new knowledge and skills increases research institutions' pressure to attract global talent.…”
Section: Literature Reviewmentioning
confidence: 99%